2021
DOI: 10.1002/ps.6656
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of different deep convolutional neural networks for detection of broadleaf weed seedlings in wheat

Abstract: BACKGROUND In‐field weed detection in wheat (Triticum aestivum L.) is challenging due to the occurrence of weeds in close proximity with the crop. The objective of this research was to evaluate the feasibility of using deep convolutional neural networks for detecting broadleaf weed seedlings growing in wheat. RESULTS The object detection neural networks, including CenterNet, Faster R‐CNN, TridenNet, VFNet, and You Only Look Once Version 3 (YOLOv3) were insufficient for weed detection in wheat because the recal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 58 publications
0
26
0
Order By: Relevance
“…Finally, in 2008, Li, L. introduced a collection digital data device for dynamic monitoring; the device includes an infrared image sensor, an ARM and DSP-based data processing module, a GPS system, and a data link ( Li et al., 2004 , 2008 ; Yuan et al., 2006 ). In 2021, the author participated in publications such as “Evaluation of different deep convolutional neural networks for detection of broadleaf weed seedlings in wheat” ( Zhuang et al., 2021 ). Therefore, the author with the most publications is an expert focussed on technological development solutions for digital agriculture.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, in 2008, Li, L. introduced a collection digital data device for dynamic monitoring; the device includes an infrared image sensor, an ARM and DSP-based data processing module, a GPS system, and a data link ( Li et al., 2004 , 2008 ; Yuan et al., 2006 ). In 2021, the author participated in publications such as “Evaluation of different deep convolutional neural networks for detection of broadleaf weed seedlings in wheat” ( Zhuang et al., 2021 ). Therefore, the author with the most publications is an expert focussed on technological development solutions for digital agriculture.…”
Section: Resultsmentioning
confidence: 99%
“…The authors found that the ratios of positive and negative images in the training dataset affected the performances of the neural networks for weed detection. Recently, Zhuang et al 51 reported that increasing training image sizes from 200 × 200 pixels to 400 × 400 pixels increased the F 1 scores of DenseNet and ResNet, but generally decreased those of AlexNet and VGGNet for the detection of broadleaf weed seedlings growing in wheat (Triticum aestivum L.). However, the authors noted that increasing training image numbers increased classification accuracy, diminishing the differences in training image sizes.…”
Section: Discussionmentioning
confidence: 99%
“…In the event of irregularly shaped plants or patches of plants, multiple bounding boxes were drawn to encompass the entirety of the plant features. Labeling partial sections of irregularly shaped plants has been shown to be beneficial to object detectors (Sharpe et al 2018(Sharpe et al , 2020aZhuang et al 2022), so these irregular features were not ignored. In any given image, both plant species could be present, so they were labeled accordingly.…”
Section: Image Processing and Data Annotationmentioning
confidence: 99%